2007
DOI: 10.1111/j.1523-536x.2007.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Postpartum Breastfeeding and Acculturation among Hispanic Women

Abstract: This cross-sectional study provides evidence of a correlation between acculturation and immediate postpartum breastfeeding, where higher acculturation is associated with lower odds of exclusive breastfeeding. Additional research is needed to understand how the process of acculturation may affect short- and long-term breastfeeding behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 46 publications
3
30
2
2
Order By: Relevance
“…Language spoken, as a proxy for acculturation, is strongly and positively correlated with breastfeeding among Hispanics. 21,22 We then randomly assigned WIC participants to 1 of 3 study arms of the telephone peer counseling program in 4 LWAs. The intervention began during pregnancy and continued postpartum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Language spoken, as a proxy for acculturation, is strongly and positively correlated with breastfeeding among Hispanics. 21,22 We then randomly assigned WIC participants to 1 of 3 study arms of the telephone peer counseling program in 4 LWAs. The intervention began during pregnancy and continued postpartum.…”
Section: Methodsmentioning
confidence: 99%
“…As noted above, this is a common finding. 21,22 Indeed, differences in breastfeeding rates by language among Hispanics exist nationally. Data from the National Immunization Survey for the years [2005][2006][2007] indicate that 48% of Hispanics who conducted their interviews in Spanish and whose child was ever enrolled in WIC exclusively breastfed for at least 3 months (n = 7107) compared with 25%…”
Section: Figurementioning
confidence: 99%
“…It may be that most participants in our study were more acculturated to the Mexican culture than to the mainstream culture (based on nativity), and the Mexican cultural value of familia (close family support that is a common value among women of Mexican origin) contributed to the low levels of depression symptom severity we observed. This premise is supported by Wambach et al (2016) and Gorman et al (2007) who reported that less acculturated mothers were more supportive of breastfeeding and believed it to be consistent with their cultural beliefs.…”
Section: Discussionmentioning
confidence: 78%
“…The Centers for Disease Control and Prevention (2015) reported that Hispanic women begin formula feeding in addition to breastfeeding at higher rates than women of other races or ethnicities. In a study of postpartum women, Gorman et al (2007) compared less acculturated Spanish-speaking women, more highly acculturated English-speaking Hispanic women, and non-Hispanic White, English-speaking women and found that the more highly acculturated Hispanic women had the lowest rates of exclusive breastfeeding among the three groups.…”
Section: Hispanic/mexican American Women and Breastfeedingmentioning
confidence: 99%
“…English speaking Hispanics comprised mothers who identified as primarily English speaking. This division of Hispanic families based on primary language was an effort to minimize the heterogeneity of acculturation within our Hispanic subsample (i.e., Badr, 2001; Gorman, Madlensky, Jackson, Ganiats & Boies, 2007). See Table 1 for demographics for the total sample and by ethnic group.…”
Section: Methodsmentioning
confidence: 99%